Hands-on with MS Teams - Gordon, Adam (Packt Publishing, 2024)
Embark on a transformative journey through Microsoft Teams with this expertly designed video course. Starting with foundational overviews, you'll gain insights into network planning, configuration, and policy management across multiple platforms. By the end of the first section, you'll have a solid understanding of the essential tools and configurations needed for an efficient Teams setup. Moving forward, this course delves into the intricacies of managing teams and memberships. From creating teams to upgrading existing resources, and configuring settings and permissions, you'll learn how to maintain an organized and productive environment. Each video offers step-by-step guidance, ensuring that you can follow along and implement changes in real-time. The latter sections of the course focus on guest access, chat and collaboration experiences, meeting management, app policies, and security compliance. You will explore advanced features like dynamic membership, external access, live event configurations, and legal hold implementations. This course ensures that you not only master the functionalities of Microsoft Teams but also understand how to leverage these features for optimal performance and security within your organization.
Online resource; title from title details screen (O'Reilly, viewed August 5, 2024)
Keywords: Microsoft Team manager; Microsoft Office; Groupware (Computer software); Telecommuting; Internet videoconferencing; Logiciels de groupe; Visioconférences sur Internet; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet